Action thresholds of wet rice arthropods for pest management decision-making in Malaysia - Syed Hassan, Syed Tajuddin (Universiti Putra Malaysia Press, 1997)
Action thresholds to aid pest population management decision-making of 11 categories of wet rice arthropods are suggested in terms of mean population density per hill (x) and proportion of infestation (P(I)) of the field sampling units. The thresholds are the (x) and P(I) values at the point of saturation of a polynomial regression curve obtained by plotting (x) against P(I) for each arthropod category. The respective values for pests are: 3.38, 0.92 (Nephotettix spp.), 6.28, 1.00 (Nilaparvata lugens), 1.37, 0.72 (Cnaphalocrocis medinalisPyralidae), 2.42, 0.90 (Recilia dorsalis), 3.81, 0.97 (Sogatella furcifera), and for predators are: 3.89, 0.98 (Cyrtorhinus lividipennis), 2.39, 0.85 (Anatrichus pygmaeus- Diptera), 2.02, 0.82 (Odonata), 1.65, 0.81 (Casnoidea sPP), 1.61, 0.64 (paederus fuscipes), and 1.60, 0.69 (spiders). P(I) is significantly (P<O.OOl) affected by arthropod category and growth stage of the crop. The observed pel) indicated high fits (most i>0.90) to clumped- and Poisson-based distribution models.